Application of quality by design (QbD) to formulation and processing of naproxen pellets by extrusion–spheronization. (29th July 2014) - Wang, Junlin; Kan, Shuling; Chen, Tong; Liu, Jianping
Abstract: The aim of this research was to apply quality by design (QbD) to the development of naproxen loaded core pellets which can be used as the potential core for colon-specific pellets. In the early stages of this study, prior knowledge and preliminary studies were systematically incorporated into the risk assessment using failure mode and effect analysis (FMEA) and fishbone diagram. Then Plackett–Burman design was used to screen eight potential high risk factors (spheronization speed, spheronization time, extrusion speed, drying method, CCMC-Na concentration, lactose concentration, water concentration and Tween 80 concentration) obtained from the above risk assessment. It was discovered that out of the eight potential high risk factors only three factors (spheronization speed, extrusion speed and CCMC-Na concentration) had significant effects on the quality of the pellets. This allowed the use of Box–Behnken design (BBD) to fully elucidate the relationship between the variables and critical quality attribute (CQA). Finally, the final control space was established within which the quality of the pellets can meet the requirement of colon-specific drug delivery system. This study demonstrated that naproxen loaded core pellets were successfully designed using QbD principle.